CHANGES IN PRODUCTION POTENTIAL IN AGRI-FOOD SECTOR IN POLAND - Adam Pawlewicz; Zbigniew Brodziński (Annals of the Polish Association of Agricultural and Agribusiness Economists)
The aim of studies and analyzes was to identify the directions of changes that took place in the Polish agro-food sectoron the background of the whole economy of the country. The analysis focused on the manufacturing potential and wasbased on information on labor resources, the value of the means of production and investment outlays in the food industryand agriculture. The analysis period covered the years 2005-2015, which was used to present the linear regression linefor 2016-2017. On the basis of the research, there has been observed a decline in employment in the food industry andan increase in the number of people employed in agriculture. At the same time, the gross value of fixed assets in thesedivisions is growing, with their share in the overall economy decreasing. Also, the value of investment outlays in the foodand agriculture sectors increased during the period, but in the case of the food industry the whole economy is decreasing,while in agriculture it is growing slightly.